The effect of silicon dioxide nanoparticles combined with entomopathogenic bacteria or fungus on the survival of Colorado potato beetle and cabbage beetles - Shatalova, Elena I. (Nanomaterials)
Three types of modified silicon dioxide nanoparticles (SiO2, 10-20 nm) with additives of epoxy, silane and amino groups, used independently and in combination with the entomopathogenic bacteria Bacillus thuringiensis subsp. morrisoni and fungus Metarhizium robertsii were tested against Colorado potato beetle (Leptinotarsa decemlineata) and cabbage beetles (Phyllotreta spp.). All three nanoparticles were found to have an entomocidal effect on Colorado potato beetle larvae and crucifer flea beetles when ingested. Increased susceptibility of insects to B. thuringiensis or M. robertsii blastospores and their metabolites was shown after exposure to the modified silicon dioxide nanoparticles. The potential of modified silicon dioxide nanoparticles to enhance the efficiency of biopesticides based on the bacteria B. thuringiensis and fungi M. robertsii is considered in the paper.